Preparation of an associative thickener for digital printing of nylon carpet. Issue 3 (7th May 2019) - Zhou, Chang-E; Niu, Haidan; Zhang, Qing; Li, Huixia; Kan, Chi Wai; Sun, Chang; Du, Jinmei; Xu, Changhai
Abstract : Purpose: This paper aims to prepare an associative thickener base on two polyacrylate-based copolymers, which can be used for digital printing of nylon carpet with enhanced performance. Design/methodology/approach: An associative thickener was prepared by compounding two polyacrylate-based copolymers, cationic starch and polyacrylic acid; and mediated by polyethylene glycol and polyacrylamide crosslinker. The formulation of the associative thickener was optimized by using the orthogonal array testing strategy. The stability of the associative thickener was investigated by measuring effects of temperature, electrolytes, storage time and auxiliaries on viscosity. The associative thickener was compared with a commercial thickener by evaluating their performance in digital printing of nylon carpet. Findings: The associative thickener provided same color strength and fastness in the printing of nylon carpet as the commercial one, but was more easily washed off for a better hand feeling of the printed carpet. Practical implications: The prepared associative thickener can be applied for digital printing of nylon carpet. Originality/value: The associative thickener can be facilely prepared from commercially available chemicals and suitable for digital printing of nylon carpet.